INHERITANCE BY CONTRACT COMPLEX INSTITUTION: PROBLEMATIC ISSUES ACTUALIZATION - Pilipsons, Edvards (Administrative and Criminal Justice, 2015)
Inheritance by contract exists as a complex legal institution, including both agreements and unilateral transactions mediating the alienation of property objects. Simultaneously inheritance by contract appears as a complex legal compound and transplant. Legal doctrine and legislative practice devote insufficient attention in this legal phenomenon research. This article deals with this complex institution problematic actualization highlighting key points for future analysis and research.